Demand for finance PH.D.'s : 1989-1998 - Ang, Chow Yang (2008)
Our study would help finance doctorates by providing information on what the employers are looking for. We focus our study on the Top 20, Top 21-50 and Other Finance Departments that make up an important and hefty part of the overall finance hire market. The four most desired areas of expertise are: corporate finance and business finance; investments; bank management and financial markets and institutions; and international finance.